Portrait of Living Hadith during The Times of The Companions of The Prophet (Typology of The Narration of QS. al-FÄtiá¸¥ah by AbÅ« Sa'Ä«d Al-KhudrÄ«) - Althaf Husein Muzakky; Amyaz Bill Aufaq (UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
This article discusses the narration of the hadith performed by the companions Abu Abu Sa'i@d Al-Khudri. As a teenager in the days of the prophet, he was referred to as the great narrator of the hadith. The then interesting thing from Sahabat Abu Sa'i@d Al-Khudri is his persistence in narrating the hadith not statistically but dynamically, because according to him the function of the hadith is not only a source of Islamic teachings but also social cultural resources. Through library study method and content analysis using knowledge sociology, it is found that al-Fa@tihah narrative of Abu Sa'i@d Al-Khudri has two types of typology, an informative type as a form of teachings of hadith prophets and types of performative embodiments of application or living hadith as a tradition that is not contrary to the hadith of the prophet.",